Pathogenesis of HIV infection - Hassan M. Naif (MDPI AG, 2013)
Over the past three decades of intense research on the contribution of viral and host factors determining the variability in HIV-1 infection outcome, HIV pathogenesis is still a fascinating topic that requires further study. An understanding of the exact mechanism of how these factors influencing HIV pathogenesis is critical to the development of effective strate- gies to prevent infection. Significant progress has been made in identifying the role of CCR5 (R5) and CXCR4 (X4) HIV strains in disease progression, particularly with the persistence of R5 HIV-1 strains at the AIDS stage. This indicates that R5 strains are as fit as X4 in causing CD4+ T cell depletion and in contribution to disease outcome, and so questions the prerequisite of the shift from R5 to X4 for disease progression. In contrast, the ability of certain HIV strains to readily use CXCR4 for infection or entry into macrophages, as the case with viruses are homozygous for tropism by CCR5delta32. This raises another major paradox in HIV pathogenesis about the source of X4 variants and how do they emerge from a relatively homogeneous R5 viral population after transmission. The interactions between viral phenotypes, tropism and co-receptor usage and how they influence HIV pathogenesis are the main themes addressed in this review. A better understanding of the viral and host genetic factors involved in the fitness of X4 and R5 strains of HIV-1 may facilitate development of specific inhibitors against these viral populations to at least reduce the risk of disease progression.